Phraseological locutions in modern Arabic political discourse and its translation peculiarities. (Journal of Oriental Studies, 2016)
In the article the using of phrase logical locutions as one of the peculiarities of political discourse texts has been shown. Phrase logical locutions make a function of emotional influence on the recipient. From translational point of view phrase logical locutions feature big difficulties, because of their specific national coloring.
Keywords: phrase logical locutions; political discourse; ways of translation